THU0225 Role of the IL-12/IL-35 balance in SJÖGREN'S syndrome. (15th June 2017) - Fogel, O; Rivière, E; Seror, R; Nocturne, G; Boudaoud, S; Ly, B; Gottenberg, J-E; Guern, V Le; Dubost, J-J; Nititham, J; Taylor, K; Chanson, P; et al.
Abstract : Background: An interferon (IFN) signature is involved in the pathogenesis of primary Sjögren's syndrome (pSS), but whether the signature is type 1 or 2 remains controversial. Mouse models and genetic studies suggested the involvement of T helper 1 and type 2 IFN pathways. Likewise, polymorphisms of interleukin 12A gene ( IL-12A ), which encodes for IL-12p35, have been associated with pSS. IL-12p35 subunit is shared by 2 heterodimers, IL-12 and IL-35. Objectives: To confirm the genetic association of IL-12A polymorphism and pSS and elucidate the involvement of the IL-12/IL-35 balance in pSS by functional studies. Methods: The genetic study involved 673 patients with pSS from 2 French pSS cohorts and 585 healthy French controls. Functional studies were performed on sorted monocytes, stimulated or not. IL-12A mRNA and IL-12 and IL-35 protein levels were assessed by qRT-PCR and by ELISA and a multiplex kit for IL-35 and IL-12, respectively. Results: We confirmed the association of the IL-12A rs485497 polymorphism and pSS and found an increased serum protein level of IL-12p70 in pSS patients carrying the risk allele (p=0.016). Serum level of IL-12p70 was greater in patients than controls (p=0.0001), especially patients with more active disease (p=0.05); conversely IL-35 level was decreased in patients (p=0.0001) especially in patients with a more active disease (p=0.05). Conclusions: Our findings emphasize the involvement of the IL-12/IL-35 balance in the pathogenesis of pSS. Serum IL-35 level was associated with low disease activity, in contrast to serum IL-12p70 level, which was rather associated with a more active disease. Acknowledgements: We thank Dr Odile Devergne (Université Paris Descartes, AP-HP, Hôpital Necker, Paris) for her expertise on the IL-35 ELISA kit to ensure the quality and reproducibility of this test. The authors thank the following investigators of the ASSESS cohort prospective cohort of patients with Sjögren's syndrome (all in France) who recruited the patients and conducted follow-up: A. L. Fauchais (Limoges), S. Rist (Orleans), V. Le Guern (Paris), G. Hayem (Paris), J. Sibilia (Strasbourg), J. Morel (Montpellier), A. Saraux (Brest), A. Perdriger (Rennes), X. Puechal (Le Mans), E Hachulla (Lille) and V. Goeb (Rouen). The authors thank Dr J. Benessiano, S Tubiana and all staff members of the Bichat Hospital Biological Resource Center (Paris) for their help in centralizing and managing biologic data collection from the French ASSESS, Disclosure of Interest: None declared